An Introduction to Competition Commission in India: Promoting fair competition and protecting consumer interests (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Section 7 provides for the establishment of competition commission of India. Competition is a situation in a market, in which sellers independently strive for buyer’s patronage profits, sales or market share. It is a means of reducing cost and improving quality. It accelerates growth and development. It preserves economic and political democracy. It shall be the duty of the Commission to eliminate practices having adverse effect on competition, to promote and sustain competition, protect the interests of consumers and ensure freedom of trade carried on by other participants, in markets in India. The Commission may inquire into any matter related with anti-competitive agreement. Key words Competition, Agreement, Association, Person, MRTP etc.